Respectable Deviance and Purchasing Medicine Online Opportunities and Risks for Consumers - Sugiura, Lisa (Palgrave Studies in Cybercrime and Cybersecurity, 2018)
This is a unique interdisciplinary exploration of the contemporary phenomenon of online medicine purchasing. In this research, Sugiura provides a criminological understanding of the sale of online medicines as well as the traditional illegal markets. Crucially, the practice is investigated from the perspective of web users, moving beyond the headlines and warning campaigns to contextualise the provision of medicines online, to describe this practice and subjective accounts of purchasing medicines from the Web. Drawing together established deviance theories, Respectable Deviance and Purchasing Medicine Online considers the construction of online medicine purchasing, the justifications presented to challenge how it is labelled, and how the behaviour is managed to show how the framing of risks and deviance is challenged online. Offering a much-needed a critical overview of the UK healthcare regulatory system, Sugiura also analyses literature, data and policy documents originating from different countries highlighting that the geographical locations of participants in web forums, online surveys and non-face-to-face interviews cannot always be verified. With broad implications for regulation and safety surrounding medicines online, this innovative and timely study contributes to current online healthcare debates and broadens our understanding of cybercrime. It will be of particular interest to scholars of cybercrime and those interested in the changing nature of deviance.